MUHAMMADIYAH SEBAGAI GERAKAN PEMBAHARUAN PENDIDIKAN ISLAM - Aphil Barroch Mahesa; Faisal Ramadhan; Tri Wirahadi Kusuma; Muhammad Farid Alfian; Febri Nur Hudanansyah (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Muhammadiyah is an Islamic reform organization that has had a major impact on the progress of Muslims in Indonesia. The reforms carried out by Muhammadiyah include multidimensional, such as in education, health, economy and culture. In the field of education, Muhammadiyah undertook the modernization of Islamic education, which is essential for the development of Islamic education in Indonesia. Muhammadiyah refined the Islamic education curriculum by incorporating Islamic religious education into public schools and secular knowledge to religious schools. The concept of HIS med the Qur'an, which was launched by Muhammadiyah, could mean that public schools plus Islamic subjects became a model not only for educational institutions under Muhammadiyah, but also used by other Muslim groups, which made education an area of concern. In addition, Muhammadiyah also organized the modernization of madrasah by integrating it with the boarding system (pesantren). Modernization takes place intensely in the form of the introduction of the institutional elements of modern education and the subjects of modern science. The renewal of Muhammadiyah education gave rise to various advances in various areas of Indonesian society. The historicity of Muhammadiyah as an educational movement can be referred to the formulations of the goals of Muhammadiyah's presence from 1921 to 1971 which describe education as the basis of its movement and steps. Muhammadiyah wants to provide a new perspective that education is holistic integrative, not in a partial dichotomous area, which can contribute to the development and progress of the nation.